Removal of Different Thicknesses Influences the Repair Bond Strength of Dental Resin Composites - Kai Yu (Frontiers Media S.A., 2021)
This study investigates the repair bond strength of aged resin composites after removing different thicknesses, determine the repair performance using the same or different resin composites and describe the treated surfaces after ageing. Seventy simulated class I cavities were prepared in extracted human third molars were randomly divided into two groups and restored with a nanofilled (Filtek Z350) or a microhybrid (Clearfil APX) composite. Five specimens without ageing in each group acted as a positive control for microtensile bond strength (MTBS) test. After thermocycling, each group was randomly divided into two subgroups: Group RT1, 1 mm removed and Group RT3, 3 mm removed, followed by roughening. Ten specimens in each subgroup were repaired with the same or different composites, and MTBS tests were conducted. The surface roughness (Sa), and water contact angle of the remaining five specimens in each subgroup were measured. In every combination group, Group RT3 showed significantly higher MTBS values than Group RT1, and identical composite was not compulsory for higher repair bond strength. Removal thickness had no significant effect on the Sa in same composite group. In both the Z350 and APX groups, the water contact angle decreased with increasing removal thickness.